Theologie und Gesellschaft im 2. und 3. Jahrhundert Hidschra: eine Geschichte des religiösen Denkens im frühen Islam - Ess, Josef van (De Gruyter, 1992)
pp. 186-233 (the Ibāḍiyya); p. 268-270 (Wāṣil’s relation to Khārijīs and Murji’īs); pp. 270-273 (Wāṣil’s political ideas); pp. 396-398 (al-Aṣamm); 460-469 (the Khārijīs in al-Jazīra); pp. 572-600 (the Khārijīs in Sistān); pp. 601-604 (the Ibāḍīs in Sistān); pp. 612-624 (the Khārijīs in middle and South Iran); pp. 655-659 (the Khārijīs and the Ibāḍīs in Mekka); pp. 666-668 (the Khārijīs in Medina); pp. 709-712 (ʿUmān and Ḥaḍramaut); pp. 719-722 (contrary movements against the Shīʿa: the Ibāḍīs).
Keywords: Kharijisme

Falsafat al-Khawārij - Quṭb, Sayyid (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)
Keywords: Kharijisme

al-Farq bayna ‘l-Ibāḍiyya wa’l-Khawārij - Iṭfayyish, Abū Isḥāq Ibrāhīm (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)
Keywords: Kharijisme

Hal al-Ibāḍiyya Khawārij? - Bā, ʿUmar b. al-Hājj Muḥammad Ṣālih (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)
Keywords: Kharijisme

قراءة جديدة في مواقف الخوارج وفكرهم وأدبهم - اليونس, عبد اللطيف (الثقافة, 1992)
Keywords: Kharijisme